Desempenho diagnóstico da punção aspirativa por agulha fina no diagnóstico dos tumores de glândulas salivares maiores: avaliação da casuística de um centro universitário de referência oncológica - Muniz, Laís Borges (2013)
A fine-needle aspiration (FNA) is a technique used in the diagnosis of salivary glands tumors (SGT) for decades in various institutions in different countries. The aim of this study was to evaluate the diagnostic performance of FNA in SGT in a referral university oncology center in Brazil and compare the results between the anatomical sites of major salivary glands. The retrospective period of analysis reviewed 32.502 cytopathology exams, which 1.793 of head and neck, and of these 183 from major salivary glands. Eighty-one exams of SGT contained subsequent histopathologic exams. Posteriorly, the conclusions cytological and histopathological from these exams were then compared statistically to estimate the ability of FNA in identifying neoplastic or malignant nature of the SGT. The results regarding the ability of FNA in identifying neoplastic nature in parotid tumors for sensitivity and accuracy was 100%, while for submandibular tumors was 92.8% and 93.3% respectively, and 100% for specificity. The ability of FNA in identify the malignant nature in parotid tumors the results was 93.3% for sensitivity, 90% specificity and 92.5% accuracy, and in the submandibular the values was 100% for all variables. There was a high frequency of nondiagnostic FNA, especially in identifying neoplastic nature in submandibular. FNA showed high values of diagnostic performance in identifying neoplastic lesions and malignant lesions for parotid and submandibular, supporting its usefulness in the diagnosis of SGT, and highlights, in special, the importance of consider the greater frequency of non-neoplastic lesions in submandibular gland and neoplastic lesions in parotid.